Analisis Kandungan Minyak dan Lemak Pada Sampel Air Limbah di UPTD Laboratorium Lingkungan Dinas Lingkungan Hidup Provinsi Lampung - Haryadi, Andri; Sulastri (Fakultas Teknik Universitas Hamzanwadi, 2025)
Domestic wastewater pollution containing oil and grease is an environmental issue that requires serious attention. Oil and grease can disrupt water quality and affect the life of aquatic biota in it. This study aims to analyze the oil and grease content in domestic wastewater in Lampung Province. This study used an experimental method on 25 domestic wastewater samples to determine the oil and grease content using the gravimetric method according to JIS No. 24 K-0102, 1998. The results of this study obtained oil and grease content values ​​ranging from 0.2 - 3.8 mg / l, which indicates that the value is below the quality standard stipulated in the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. 68 of 2016, which is 5 mg/l. The values ​​obtained indicate that the oil and water content in the analyzed wastewater is still relatively low. However, management, supervision, and education to the public are needed to prevent an increase in oil and grease content in domestic wastewater so that it remains within safe limits for the environment.